Biophysical Stress Responses of the Yeast Lachancea thermotolerans During Dehydration Using Synchrotron-FTIR Microspectroscopy - Câmara, Antonio Anchieta; Nguyen, Thanh Dat; Saurel, Rémi; Sandt, Christophe; Peltier, Caroline; Dujourdy, Laurence; Husson, Florence (Frontiers in Microbiology, 2020)
During industrial yeast production, cells are often subjected to deleterious hydric variations during dehydration, which reduces their viability and cellular activity. This study is focused on the yeast Lachancea thermotolerans, particularly sensitive to dehydration. The aim was to understand the modifications of single-cells biophysical profiles during different dehydration conditions. Infrared spectra of individual cells were acquired before and after dehydration kinetics using synchrotron radiation-based Fourier-transform infrared (S-FTIR) microspectroscopy. The cells were previously stained with fluorescent probes in order to measure only viable and active cells prior to dehydration. In parallel, cell viability was determined using flow cytometry under identical conditions. The S-FTIR analysis indicated that cells with the lowest viability showed signs of membrane rigidification and modifications in the amide I (α-helix and β-sheet) and amide II, which are indicators of secondary protein structure conformation and degradation or disorder. Shift of symmetric C–H stretching vibration of the CH2 group upon a higher wavenumber correlated with better cell viability, suggesting a role of plasma membrane fluidity. This was the first time that the biophysical responses of L. thermotolerans single-cells to dehydration were explored with S-FTIR. These findings are important for clarifying the mechanisms of microbial resistance to stress in order to improve the viability of sensitive yeasts during dehydration.